RISK AS THE MAIN CONDITION OF INSURANCE IN INVESTMENT ACTIVITIES - Eshchanova Dauletbike Ametbekovna (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: This study aims to analyze the legal concept of "risk" within the framework of civil law theory, with a specific focus on its application to investment insurance. The research explores both the objective and subjective dimensions of risk by reviewing key perspectives from civil law scholars and examining their implications in practical contexts. Methods: A comprehensive review of civil law theories and scholarly literature was conducted to define and evaluate the characteristics and features of risk. The study focuses on identifying the dual nature of risk—objective and subjective—and assessing its relevance in the domain of investment insurance. Comparative analysis of theoretical foundations and practical applications was employed to establish a cohesive understanding. Results: The research identifies key features of risk as outlined by civil law scholars, emphasizing their significance in investment activities. The study reveals how the theoretical foundations of risk provide a structured framework for understanding its implications in the management of investment insurance. The dual nature of risk—comprising both measurable (objective) and perceptive (subjective) elements—was found to be integral to its legal characterization and practical application. Novelty: This study bridges the gap between theoretical legal analysis and practical implementation of risk management in investment insurance. By offering a detailed exploration of the dual nature of risk, the research provides a deeper understanding of its role within civil law and investment activities. This perspective enriches the existing literature and offers valuable insights for legal scholars and practitioners in the field of investment insurance.